Under-nutrition and associated factors among children on ART in Southern Ethiopia: a facility-based cross-sectional study - Chalie Marew Tiruneh; Belete Gelaw Walle; Tigabu Desie Emiru; Nigusie Selomon Tibebu; Moges Wubneh Abate; Adane Birhanu Nigat; Amsalu Belete; Eyasu Alem; Tadele Lankrew; Kirubel Eshetu (BMC, 2021)
Abstract Background Malnutrition is very common in HIV-infected individuals. Even though data from different settings are necessary to tackle it, pieces of evidence are limited especially in the case of the nutritional status of HIV-infected children. Hence, this study aims to assess the nutritional status and associated factors among children on antiretroviral therapy. Methods An institutional-based cross-sectional study was conducted among 383 HIV-positive children in Southern Ethiopia. Data were collected using an interviewer-administered questionnaire and anthropometry measurement. Data were coded and entered into Epi-Data Version 3.1 and analyzed using SPSS Version 25. Bi-variable and multi-variable binary logistic regression models were used to identify factors associated with nutritional status and variables with p-values <0.05 in multi-variable logistic regression were considered as statistically significant. Results The prevalence of wasting among HIV-positive children in Southern Ethiopiaselected Hospitals was 36.3% (95% CI, 31.6-41.0) while stunting on the same study population was 5.5% (95% CI, 3.4-7.8). Rural residence, lack of maternal education, low CD4 counts (< 500), using an unprotected water source, having a non-biological mother and recurrent oral lesion were significantly associated with wasting. Furthermore, history of hospital admission, recurrent oral lesion, low CD4 counts (< 500), advanced WHO clinical stage were statically associated with stunting with p-value < 0.05. Conclusion This study found that the prevalence of under-nutrition among HIV-positive children in Ethiopia was significantly high. Therefore, timely identification and monitoring of nutritional problems should be necessary to enhance the effectiveness of ART treatment and to prevent further related complications.